Izvor pridevnikov tipov bukov in lipov/češnjev v slovenščini - Šekli, Matej (Slavistična revija, 2019)
The article discusses the origin of the adjectives with the suffix -ov/-ev such as bukov 'of / relating to beech', lipov 'of / relating to linden', and češnjev 'of / relating to (a) cherry (tree)' derived from feminine nouns and traces their development in Slovenian. The genesis and the original word-formational function of the Proto-Slavic adjectival suffix *-ov-"/*-ev-" are presented and appended with a semantic classification of such adjectives in Slovenian, based on the lexical meaning of the head in the respective nominal phrases.
Keywords: besedotvorje; denominal adjective suffix; izsamostalniške pridevniške pripone; pomenoslovje; praslovanščina; Proto-Slavic language; semantics; Slovenian language; slovenščina; word formation